2021
DOI: 10.1016/j.jiph.2021.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in COVID-19 ICU admission rates in the Kingdom of Saudi Arabia: A simulation of the new model of care under vision 2030

Abstract: Objective Saudi Arabia has succeeded in having one of the lowest rates of COVID-19 worldwide due to the government’s initiatives in taking swift action to control both the spread and severity of the virus. However, Covid-19 can serve as a test case of the expected response of the new healthcare system under Vision 2030. This study used data from the thirteen present administrative regions of KSA to simulate the variations in ICU admission as a quality indicator in the five business units proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…Geriatric patients may have increased mortality risks as their pre-existing conditions increase and have higher requirements for interventions such as oxygen, ICU, mechanical ventilation, and longer hospital stays [ 13 - 16 ]. A study of ICU admissions for COVID-19 inpatients in the KSA revealed age, sex, and comorbidities as risk factors similar to international studies [ 17 ]. Based on the aforementioned study and a review of international studies it is reasonable to expect that the elderly in Saudi Arabia would also be at higher risk for mortality [ 18 - 21 ].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Geriatric patients may have increased mortality risks as their pre-existing conditions increase and have higher requirements for interventions such as oxygen, ICU, mechanical ventilation, and longer hospital stays [ 13 - 16 ]. A study of ICU admissions for COVID-19 inpatients in the KSA revealed age, sex, and comorbidities as risk factors similar to international studies [ 17 ]. Based on the aforementioned study and a review of international studies it is reasonable to expect that the elderly in Saudi Arabia would also be at higher risk for mortality [ 18 - 21 ].…”
Section: Introductionsupporting
confidence: 56%
“…After controlling for patient and disease factors, compared to the central BU, the northern BU had the highest mortality rate followed by the western, whose rates were 9.90 and 1.55 times higher, respectively, showing statistically significant increases, whereas the rates in the southern and eastern BUs were lowest, with rates 0.60 and 0.23 times lower, respectively, also showing statistically significant decreases. Disparities in the quality of care between BUs have been observed in ICU admissions indicating similar results with the northern and western BUs being highest and southern and eastern BUs being lowest revealing a concerning trend [ 17 ].…”
Section: Discussionmentioning
confidence: 76%
“…Complications linked to COVID-19 include bacterial pneumonia, sepsis, acute respiratory distress syndrome (ARDS), acute kidney injury, multi-organ failure, thromboembolism, and others. 8 , 9 As previously reported by several studies, health care resources throughout the world faced multiple challenges in meeting the surge in COVID-19 patients, including demand for intensive care units (ICUs) and other critical care services, the wide range of symptoms, complications, and outcomes requiring continual upgrading of treatment modalities, severe and persistent shortages of equipment and staff, and efficient distribution of the burden, among others. 9–11 Along with the toll on health care systems around the world, the COVID-19 pandemic has significantly disrupted socio-economic systems globally including food production and distribution, the supply chain, and the survival of many enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…15 The pandemic has disrupted the healthcare system just as the transition of the healthcare system under Vision 2030 has begun, providing an opportunity to measure many quality factors using this rare occurrence. 8 , 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation